Análise da aplicação de um sistema de ignição de alta potência em motores de combustão interna - Delalibera, Guilherme de Carvalho (2014)
Analysis of the use of a high power ignition, practical test (street) and dynamometer practical approach. In an attempt to improve one step of the four-stroke internal combustion engines, without the need to increase the fuel injection, so not only expecting an improvement in power and torque as well as in fuel consumption.